Effect of Different Fertilization Rates on Cyanogen and Foliage and Tuber Yields of Cassava - Yin Yin Kyawt; Achara Lukkananukool; Win Mi Htwe; Min Aung (My University, 2020)
This experiment was conducted to determine the effect of different fertilization rates on the cyanogen and yields of cassava foliage and tuber. Nine fertilization rates, three nitrogen and potassium levels (N: 0, 50, 100 kg/ha and K: 0, 100, 250 kg/ha, respectively) with constant phosphorus level (P: 50 kg/ha) (F-0:N0-P50-K0, F-1:N0-P50-K100, F-2:N0-P50-K250, F-3:N50-P50-K0, F-4:N50-P50-K100, F-5:N50-P50-K250, F-6:N100-P50-K0, F-7:N100-P50-K100, F-8:N100-P50-K250), were applied in the randomized completely block design. After one year experiment, cassava foliage and tuber were harvested, and determined the yields and cyanogen (HCNp) content. The lowest (P < 0.05) HCNp contents and the highest (P < 0.05) foliage, tuber and protein yields were observed in cassava applied with F-4 (N50-P50-K100) and F-5 (N50-P50-K250) in compare with other fertilization rates. Regarding growth characteristics, the plant height (P < 0.05) was also highest in cassava fertilized by F-4 (N50-P50-K100) and F-5 (N50-P50-K250), whereas the leaf numbers per plant and branches number per plant were highest in cassava applied with F-5 (N50-P50-K250) and F-7 (N100-P50-K100), respectively. It could be recommended that the nitrogen (N: 50 kg/ha) and potassium (K: 100-250 kg/ha) should be used to reduce cyanogen contents for safe utilization and increased cassava foliage and tuber yields.
Keywords: Cyanogen; Cassava research and cyanide